2021
DOI: 10.1152/ajpendo.00060.2021
|View full text |Cite
|
Sign up to set email alerts
|

Diet-dependent sex differences in the response to vertical sleeve gastrectomy

Abstract: Nearly 80% of patients that receive bariatric surgery are women, yet mechanistic pre-clinical studies have focused on males. The goal of this study was to determine the metabolic impact of diet- and surgery-induced weight loss in males, females, and ovariectomized females. Male and female mice were fed a 60% high-fat (HFD) diet before undergoing either vertical sleeve gastrectomy (VSG) or sham surgery. Mice either remained on HFD or were switched to a standard chow diet post-surgically. When maintained on HFD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Among the various surgeries available, SG has become increasingly popular owing to its positive effects and relatively simple and safe surgical method (Peterli et al, 2018). Currently, many mouse models are available to study the mechanisms by which metabolic surgery treats obesity and diabetes (Ding et al, 2021; Hutch et al, 2021). DIO and ob mice represented two types of obesity and responded differently to RYGB surgery (Hao et al, 2015; Mokadem et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among the various surgeries available, SG has become increasingly popular owing to its positive effects and relatively simple and safe surgical method (Peterli et al, 2018). Currently, many mouse models are available to study the mechanisms by which metabolic surgery treats obesity and diabetes (Ding et al, 2021; Hutch et al, 2021). DIO and ob mice represented two types of obesity and responded differently to RYGB surgery (Hao et al, 2015; Mokadem et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand how diet and bariatric surgery impact the small intestinal epithelium, we first initiated male C57BL/6J mice on a 16-week high-fat diet (HFD) regimen followed by surgical intervention (Figure 1A). Upon induction of diet-induced obesity, HFD fed mice underwent vertical sleeve gastrectomy (VSG), resulting in improved metabolic outcomes compared to their sham-operated counterparts as expected from previous studies in both murine models 15,16 and human patients 10,17 . Within one-week post-surgery, HFD VSG animals lost significantly more body weight than HFD sham mice, reaching weights comparable to that approached those of a parallel group of sham mice fed a low-fat diet (LFD) (Figure 1B).…”
Section: Vsg Produces Robust Metabolic Improvements In a Validated Mo...mentioning
confidence: 94%
“…As being able to study maternal gut architecture and functioning during reproductive events is limited, other research areas have to be mined for relevant findings. Studies of metabolic diseases and medical interventions have revealed sex differences in both responses and recovery as the development and pathogenesis of metabolic disorders are notably influenced by gonadal/reproductive hormones (Hutch et al, 2021). Females with early ovarian insufficiency or after they have reached menopause (hormonally similar in lacking oestradiol), have greater risk factors for developing metabolic dysfunction, in particular type 2 diabetes, with larger adipose depots, hyperglycaemia, increased liver triglycerides; all greater than in premenopausal women.…”
Section: Metabolic Disturbances Reveal Non-uniform Remodelling Gut Pl...mentioning
confidence: 99%
“…Male and female animals both see expected metabolic and body mass (loss) improvements although ovarian hormones seem necessary for the full impact as menstruating/cycling women lose more body mass in the two years following surgery than those that are post menopausal. However, in pre-clinical animal models fed high fat diets post-surgery, females were more resistant to liver lipid decreases and corresponding differences are found in human hepatic gene expression key regulators of lipid metabolism and inflammation (reviewed by Hutch et al, 2021). These observations emphasise the importance of appropriate post-surgical diets to achieve maximum benefits in the same way that there needs to be improved post lactation nutritional guidance for females.…”
Section: Summary: Enteroplasticity Of Lactation Framework: Providing ...mentioning
confidence: 99%
See 1 more Smart Citation